Extra-adrenal Mesenteric Pigmented Paraganglioma: A Rare Case Report - Shah, Pinal; Nishal, Arpita; Patel, Himanshu; Jayani, Parmita; Gujrati, Sheetal (Annals of Pathology and Laboratory Medicine, 2020)
Paragangliomas are rare neoplasms that arise from neural crest cells of the autonomous system. It has been estimated that 5% to 10% of paragangliomas occur in extra-adrenal sites, which can extend from the upper cervical region to the pelvis, parallel to the autonomic nervous system. This distribution corresponds to the embryologic development of the paraganglia from neural crest cells. Rarely, extra-adrenal paragangliomas can also occur outside this distribution. Herein, we present a case of a 70-year-old female with history of abdominal pain, in whom an abdominal mass was identified during ultrasonography. CT scan shows solid cystic mass arising from the right side of the pelvic cavity. Exploration laparotomy reveal well-circumscribed, encapsulated, ovoid and blackish mesenteric mass. After thorough microscopic and immunohistochemistry examination, the features were that of Pigmented Paraganglioma. This case report expands the morphologic spectrum of extra-adrenal paragangliomas and emphasizes the need to consider these tumors in the differential diagnosis of pigmented neoplasms.